The Users’ Experiences in Processing Visual Media for Creative and Online Learning Using Instagram - Mohammad Salehudin* (RU Publications, 2021)
The aims of the recent study were; analyzing the effect of creative and online learning using Instagram on the ability to create new products in the technology and learning media course, and determining the level of users’ experience in processing visual media through the Canva application on android. Quantitative approach with this research was carried out through a quasi-experimental research model because it measured the post-test was applied to 58 students as the respondents in two experimental and control classes. This study used two instruments; the cognitive learning outcome questionnaire according to the subject to get the students’ ability to create new products, and the second instrument was taken from ueq-online.org in the Indonesian version to know the users' experience in processing visual media. The data were analyzed using one-way ANOVA, mean and standard deviation assisted by IBM SPSS Statistics 24.0. The results demonstrated that the effect of creative and online learning using Instagram on the ability to create new products in The Technology and Learning Media course was found significant at 0.028 <0.05 which meant it could be applied well. Meanwhile, the level of users' experience in processing the visual media application Canva on Android had the highest score on the Stimulation scale at 1.59, categorized "Very Good" and the lowest score was on the Novelty scale at 0.93, categorized "Above Average". With the strong creative encouragement to create new products, the students were able to process their own visual media which were tailored to the agreed digital visual designs and were published on Instagram.